2022
DOI: 10.1002/fft2.137
|View full text |Cite
|
Sign up to set email alerts
|

A meta‐analysis on the trust in agrifood supply chains

Abstract: The agrifood literature suggests that trust is one of the most prominent and critical aspect for not only the effectiveness of collaboration, but also for improving sustainability performance. In this sense, the understanding of how trust works in agrifood supply chains is essential to find better paths to improve the functioning of those structures. The purpose of this article was to carry out a meta-analysis on the relationships of trust among the stakeholders in agrifood supply chains, to obtain data on pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 107 publications
0
15
0
Order By: Relevance
“…The qualitative method chosen was interviewing, as Assis et al (2022) observed in their work that it was the most used method for qualitative research on trust in the agri-food area. The purpose of the research interview is to explore the views, experiences, beliefs and/ or motivations of individuals on specific subjects.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The qualitative method chosen was interviewing, as Assis et al (2022) observed in their work that it was the most used method for qualitative research on trust in the agri-food area. The purpose of the research interview is to explore the views, experiences, beliefs and/ or motivations of individuals on specific subjects.…”
Section: Methodsmentioning
confidence: 99%
“…According to the work of Assis et al (2022), conducted specifically in the agri-food area, despite being a central and transversal theme, trust has not been shown to be much studied in the last 11 years. After performing a meta-analysis on the subject, the authors concluded that research on trust linked with the areas of management and sustainability of agri-food supply chains is small and can be increased.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of chemometric or statistical tools helps to compare and analyse the differences between the normal model and the substance under test to determine if differences exist. In addition, traditional food traceability tools often use blockchain technology, barcodes or traceable packaging to prove the origin of a food product, but with the growth of the transportation industry, the same batch of food ingredients may come from multiple regions of the world ( Assis et al, 2022 ). The mixture of food properties from multiple regions makes it difficult to clearly trace multiple sources with traditional traceability tools, in which case the creation of individual source properties through the use of metabolomics of the database.…”
Section: Applications Of Metabolomics In Food Analysismentioning
confidence: 99%
“…To maintain the fresh quality of postharvest FVs, scientists and researchers are endeavoring to develop preservative techniques. In particular, it has been noted that the coronavirus pandemic has raised an alarming global situation for the supply chain of agrifood, including fresh FVs (Assis et al., 2022). As the last and most crucial step of the global supply system of fresh FVs, storage or preservation is essential to sustain the supply with reduced postharvest loss, which poses a challenge to the current preservation technologies (Lopez‐Polo et al., 2021).…”
Section: Introductionmentioning
confidence: 99%